2018
DOI: 10.1111/2047-3095.12225
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Nursing Outcomes and Interventions to Older Adults Care with Risk or Frail Elderly Syndrome: Proposal of Linkages Among NOC, NIC, and NANDA‐I to clinical practice

Abstract: OBJECTIVE Select and validate outcomes from Nursing Outcomes Classification and interventions from Nursing Interventions Classification for diagnoses Risk for Frail Elderly Syndrome and Frail Elderly Syndrome/NANDA International. METHODS A consensus study with 15 gerontological nursing specialists. Data were collected by a Google forms instrument developed by the research team and analyzed using descriptive statistics. RESULTS For the risk diagnosis, 11 outcomes and seven interventions were validated. For the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 30 publications
1
11
0
3
Order By: Relevance
“…Still in terms of knowledge about the object under investigation, the self-reported experience of the experts in relation to the use of the NOC is similar to that observed in other studies (19,22) . However, it should be highlighted that if, on the one hand, the clinical experience of the experts in the use of the NOC in care is still incipient, on the other, they considered themselves experienced in the use of the nursing process and of standardized language systems in general in the three areas of performance.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Still in terms of knowledge about the object under investigation, the self-reported experience of the experts in relation to the use of the NOC is similar to that observed in other studies (19,22) . However, it should be highlighted that if, on the one hand, the clinical experience of the experts in the use of the NOC in care is still incipient, on the other, they considered themselves experienced in the use of the nursing process and of standardized language systems in general in the three areas of performance.…”
Section: Discussionsupporting
confidence: 82%
“…Considering that in validation studies the experts must have knowledge about the phenomenon under investigation (18)(19) , it was decided to select experts with clinical experience in cardiovascular nursing and/or PC. Despite the efforts to obtain an equivalent number of experts with experience in both areas, a greater number of experts with clinical experience in cardiovascular nursing participated in the study, which can be explained by the fact that PC is a new specialty in the health area (20) .…”
Section: Discussionmentioning
confidence: 99%
“…Although no validation studies have been identified with which to compare the psychometric tests in this study, the usefulness of KPM has been demonstrated in other studies. As such, KPM has been validated for certain nursing diagnoses, Lucena et al [26] validated KPM using a group of experts for the following nursing diagnoses: Risk for Frail Elderly Syndrome and Frail Elderly Syndrome. KPM was included in the care plan of a patient with long-term left ventricular assist device (associated with the nursing diagnosis Acute pain) [27].…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, further studies have been carried out in other countries to increase the knowledge and applicability of the NOC outcomes, although each outcome has undergone its own research and development process. Validation by an expert panel has been used in certain nursing diagnoses [26,27], as well as correlation with other standards for assessing activities of daily living and functional status in nursing homes [28]. However, there are no known studies on the psychometric properties and cultural adaptation of KPM in countries other than the United States of America, despite this being considered particularly important in pain research [21,29].…”
Section: Introductionmentioning
confidence: 99%
“…The use of terminologies, such as NANDA-I, NOC, and NIC, facilitates and organizes content needed by nurses, thus enabling evidence-based practice (Lucena, Argenta, Almeida, Moorhead, & Swanson, 2019). In addition to this, linkages among the three terminologies can assist nurses in making decisions about the desired outcome and appropriate interventions for a specific nursing diagnosis (Park, 2014).…”
Section: Introductionmentioning
confidence: 99%